2016
DOI: 10.1155/2016/3942613
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tungsten Oxide Nanorod, Its Application on Textile Material, and Study of Its Functional Properties

Abstract: Nanomaterial and its application in textiles are emerging as vast and diverse field due to enhanced functionalized characteristics. This study emphasizes the fabrication of tungsten trioxide nanostructured rods and analyzes its electrostatic and ultraviolet resistance properties. These nanorods are synthesized by hydrothermal method. Through hydrothermal method rod like nanostructures were grown on polyester fabric as it withstands curing temperature easily. The growth mechanism of the film is investigated. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A. Nikitin et al synthesized iron oxide nanorods via microwave irradiation method and found it most suitable for enhanced magnetic hyperthermia [15]. Functional properties of tungsten oxide based nanorod were studied by A. Azeem et al in which they reported voltage dependent tunable transmittance modulation properties of the same [16]. N. W. Kim et al presented a facile synthesis process for the fabrication of high-quality cerium oxide nanorods with different diameters via common ion effect method [17].…”
Section: Introductionmentioning
confidence: 99%
“…A. Nikitin et al synthesized iron oxide nanorods via microwave irradiation method and found it most suitable for enhanced magnetic hyperthermia [15]. Functional properties of tungsten oxide based nanorod were studied by A. Azeem et al in which they reported voltage dependent tunable transmittance modulation properties of the same [16]. N. W. Kim et al presented a facile synthesis process for the fabrication of high-quality cerium oxide nanorods with different diameters via common ion effect method [17].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al deposited aluminum-doped ZnO (AZO) on polyester fabric using magnetron sputtering and also evaluated UPF (362), water repellency, and infrared emissivity with respect to the thickness of modified fabrics. Tungsten oxide modified polyester fabrics prepared using a two-roll padding technique achieved a UPF of 108.1 in the UVB region . Our group has recently developed nanostructured ZnO modified cotton fabrics using the sol–gel and seed-layer-enhanced sol–gel technique for UV filter and gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten oxide modified polyester fabrics prepared using a two-roll padding technique achieved a UPF of 108.1 in the UVB region. 39 Our group has recently developed nanostructured ZnO modified cotton fabrics using the sol−gel and seed-layer-enhanced sol− gel technique for UV filter and gas sensing applications. This fabric showed a UPF of 378 with a selective detection of acetaldehyde vapor at room temperature.…”
Section: Introductionmentioning
confidence: 99%